School-related factors contributing to school dropout among adolescent girls aged 10-19 years in koboko town council, koboko district, uganda. A cross sectional study. - Likico, Emily; Afaayo, Robert (Student’s Journal of Health Research Africa, 2025)
Background: In most of those societies, the average rural parent would rather invest in the education of the son rather than the daughter. The study aims to determine the school-related factors contributing to school dropout among adolescent girls aged 10-19 years in Koboko town council, Koboko district, Uganda. Methodology The study design was cross-sectional and descriptive, and quantitative data collection techniques were used; respondents were selected using cluster sampling. Data was analyzed using SPSS version 20 and was presented in tables and transferred to Microsoft Excel 2016 for the presentation of graphs. Results 96 (26.2%) of the girls were housewives, and 222 (61.8%) of the girls did not have children. Most, 96(75.2%), had had female teachers but dropped out of school. The majority, 72(56.7%), showed they had never received support, encouragement, and motivation from teachers, but dropped out of school. The majority, 108(58.4%), who had received corporal punishment at school, sometimes dropped out of school. The majority of 130(69.5%) Schools did not have all the required resources, and the girls dropped out of school. The majority, 82(43.9%), had a distance of more than 3 km and dropped out of school. 71(39.7%) had a distance of 2-3 km from school and remained in school, followed by 69 (38.5%) who had a distance of less than 1 km and remained in school. Conclusion. School -related factors contributing to school dropout among adolescent girls aged 10-19 years were motivation by teachers, punishments in schools, availability of resources, and distance of schools from homes. Recommendations. The Koboko local government, through the District Education Officer, should do regular support supervision of the schools. To ensure schools maintain the standards and girls remain at school.